Estratégia para certificação de patentes em repositórios internacionais - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia, 2023)
Introduction: The Lattes Platform is a valuable source of information for the most diverse types of analysis, however,due to the large volume of data and filling in the information is the responsibility of the individual, it may eventually cause inconsistencies in the data entered, which emphasizes the need information validation mechanisms. Methodology: The methodological process was divided into two parts, in which the first is characterized by the collection and construction of the local database with data from patents filed in Brazil and curricula from the Lattes Platform and the second part consists of the description of the certification process of the informed patents in the curricula of the Lattes Platform. Results: A local database was built, consisting of 903,979 patent records from Espacenet and 76,619 patent records distributed in 28,581 CVs collected on the Lattes Platform, all organized and structured in a relational database. Regarding the certification process of patents registered on the Lattes Platform, it was possible to certify 44,348 patent registrations, approximately 58% of the patents were certified. Conclusion: About 1% of all CVs on the Lattes Platform contain information on the filing of patents, a base made up of more than 7 million CVs (2022). Of this amount, not all could be validated and certified on Espacenet due to inconsistency in the recorded data, highlighting the need for validation and certification mechanisms for patent data.
Strategy for patent certification in international repositoriesEstrategia para la certificación de patentes en repositorios internacionales
Keywords: Patente; Plataforma Lattes; Certificação; Indicadores; Ciência da informação